Molecular mechanism of negative autoregulation of Escherichia coli crp gene. - Hanamura, A (1991)
Transcription of the Escherichia coli crp gene encoding cAMP receptor protein (CRP) is negatively regulated by CRP-cAMP complex that binds to a specific site located downstream from the transcription start site. The binding of CRP-cAMP to this site activates transcription from a second divergent overlapping promoter. The mechanism of this negative autoregulation of the crp gene has been investigated by in vitro transcription, gel shift, DNase I footprinting, and exonuclease III protection assays. We demonstrated that the crp and divergent promoters are reciprocally and coordinately regulated by CRP-cAMP. The abortive initiation assay revealed that the divergent RNA itself is not required for the inhibition of crp transcription. Detailed binding studies revealed that CRP-cAMP stimulates the binding of RNA polymerase to the divergent promoter and thus blocks the occupation of the crp promoter by RNA polymerase.